Respon Tanaman Timun (Cucumis sativus L.) Terhadap Pemberian Pupuk Kandang Ayam dan Berbagai Konsentrasi Pupuk Organik Cair Orrin - Prasetio, Yuriko; Zulfida, Ida; Jabat, Yelfi Yana Linda Br. (JURNAL AGROPLASMA, 2023)
Cucumber (Cucumis sativus L.) of the pumpkin tribe or Cucurbitaceae is a plant that produces edible fruit. The fruit is usually harvested when it is not fully ripe to be used as a vegetable or refreshment, depending on the type. One way to add nutrients to the soil is by applying chicken manure. According to Haryanto (2016) in Rumondang et al., (2020) also explained that the use of organic fertilizers is an action to improve the environment for plant plants that can improve the quality of land in a sustainable manner and organic fertilizers are also very beneficial for increasing agricultural production both in quality and quantity. This research was conducted on the experimental garden plot of the Faculty of Agriculture, Indonesian Community Development University UPMI Medan, on Jl. Market Village Hall 12 Marindal II, Patumbak District, Deli Serdang Regency, North Sumatra Province. At an altitude of 1000 meters above sea level. With the time of research in May-July 2023. The research was carried out in a factorial manner with the basic pattern of a randomized block design (RBD) consisting of two factors. Factor I: Dosage of chicken manure (A), namely: A0 = Control, A1 = 1 Kg/Plot, A2 = 2 Kg/Plot. Factor II: Dosage of liquid organic fertilizer orrin (O), namely: O1 = Control, O2 = 5 ml/l/plant, O3 = 10 ml/l/plant. The results showed that the single effect of giving chicken manure at level A2 (2 kg/plot) had an effect on increasing the growth of plant length, (at the age of 4 weeks), number of leaves (at the ages of 2 weeks, 3 weeks and 4 weeks), number of fruits and weight. fruit. The interaction effect of giving chicken coop and Orrin liquid organic fertilizer had no effect on plant length, number of leaves, number of fruits and fruit weight. Keywords: Cucumber, Chicken Manure, Orrin Liquid Organic Fertilizer